2012
DOI: 10.1080/15389588.2011.625745
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Red Light Camera Enforcement in Cities With Camera Programs

Abstract: Objective: To obtain information on attitudes and experiences related to red light camera enforcement in cities with camera programs and in Houston, Texas, where cameras were removed after voters rejected the program in November 2010. Methods:Telephone surveys were conducted with 3,111 drivers in 14 large cities (population greater than 200,000) with long-standing red light camera programs and 300 drivers in Houston, using random samples of landline and cellphone numbers. For analyses combining responses from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An autoregressive integrated moving average time series analysis of accident counts found RLCs to have an overall favorable net effect on traffic safety (Vanlaar et al 2014). It is generally agreed that RLCs have favorable effects on right-angle collisions (Aeron- Thomas and Hess 2005;McCartt and Eichelberger 2012;Retting and Kyrychenko 2002). However, both favorable and unfavorable effects are found in different studies for rear-end collisions (Huang et al 2008;Obeng and Burkey 2008;Retting et al 2003;South et al 1988).…”
Section: Previous Studies On Estimating the Effects Of Rlcsmentioning
confidence: 92%
“…An autoregressive integrated moving average time series analysis of accident counts found RLCs to have an overall favorable net effect on traffic safety (Vanlaar et al 2014). It is generally agreed that RLCs have favorable effects on right-angle collisions (Aeron- Thomas and Hess 2005;McCartt and Eichelberger 2012;Retting and Kyrychenko 2002). However, both favorable and unfavorable effects are found in different studies for rear-end collisions (Huang et al 2008;Obeng and Burkey 2008;Retting et al 2003;South et al 1988).…”
Section: Previous Studies On Estimating the Effects Of Rlcsmentioning
confidence: 92%
“…Additionally, the literature highlights claims from the public of feeling that information in public space (i.e. signage alerting roadway users of nearby cameras) was being intentionally limited, and that CE was covert by design so as to catch as many offenders as possible and drive up revenue, not to encourage safer driving behavior (Freedman et al, 1990;McCartt & Eichelberger, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies found the installation of RLCs reduces incidences of rear-end collisions (South et al, 1988), while several other studies indicated that the effects on rear-end collisions are small or even unfavourable (Huang et al, 2008;Obeng and Burkey, 2008;Retting et al, 2003). For right-angle collisions, it is generally agreed that RLCs have favourable effects (Aeron-Thomas and Hess, 2005;McCartt and Eichelberger, 2012;Retting and Kyrychenko, 2002).…”
Section: Red Light Cameras (Rlcs)mentioning
confidence: 99%